The MCM v3.3.1 degradation scheme for isoprene - M. E. Jenkin; J. C. Young; A. R. Rickard (Atmospheric Chemistry and Physics, 2015)
The chemistry of isoprene degradation in the Master Chemical Mechanism (MCM) has been systematically refined and updated to reflect recent advances in understanding, with these updates appearing in the latest version, MCM v3.3.1. The complete isoprene degradation mechanism in MCM v3.3.1 consists of 1926 reactions of 602 closed shell and free radical species, which treat the chemistry initiated by reaction with OH radicals, NO3 radicals and ozone (O3). A detailed overview of the updates is provided, within the context of reported kinetic and mechanistic information. The revisions mainly relate to the OH-initiated chemistry, which tends to dominate under atmospheric conditions, although these include updates to the chemistry of some products that are also generated from the O3- and NO3-initiated oxidation. The revisions have impacts in a number of key areas, including HOx recycling, NOx recycling and the formation of species reported to play a role in SOA (secondary organic aerosol)-formation mechanisms. The performance of the MCM v3.3.1 isoprene mechanism has been compared with those of earlier versions (MCM v3.1 and MCM v3.2) over a range of relevant conditions, using a box model of the tropical forested boundary layer. The results of these calculations are presented and discussed and are used to illustrate the impacts of the mechanistic updates in MCM v3.3.1.